An Empirical Test of Dynamic Capital Structure Model and the Speed of Adjustment: Evidence from Indonesia - Salim, Kevin Christanto B1024141018 (Jurnal Manajemen Update, 2018)
Capital structure is a never-ending topic of financial research for decades. Several prominent theories have been introduced to deal with this topic. However, previous researches have shown mixed results. This research analyzes the financing behavior of non-financial firms in Indonesia. The objectives are to ascertain firm’s readjustment behavior as explained by dynamic trade-off theory and to investigate the determinants of firm’s adjustment speed and target leverage. After that, using Partial Adjustment Model (PAM), the speed at which firms converge toward target leverage is measured. It is expected that non-financial firms in Indonesia possess target leverage and make partial adjustments toward the target over time. Panel data consist of 50 non-financial firms listed on Kompas 100 index during 2010 - 2014 are compiled to address the research problems. The empirical findings reveal tangibility and firm’s size to have positive and significant relationship with target leverage. In addition, macroeconomic variables (GDP growth and inflation rate) are found to be negatively correlated with firm’s speed of adjustment. Finally, the regression conducted on PAM shows that non-financial firms in Indonesia readjust toward their target leverage at a speed rate of 57.44% a year. In other words, it takes about 21 months for them to finish the adjustment process. These evidences conclude that the financing behavior of non-financial firms in Indonesia tend to follow dynamic trade-off theory.